2004
DOI: 10.1051/0004-6361:200400026
|View full text |Cite
|
Sign up to set email alerts
|

Organic molecules in protoplanetary disks around T Tauri and Herbig Ae stars

Abstract: Abstract.The results of single-dish observations of low-and high-J transitions of selected molecules from protoplanetary disks around two T Tauri stars (LkCa 15 and TW Hya) and two Herbig Ae stars (HD 163296 and MWC 480) ) and moderately warm (T ∼ 20-40 K) intermediate height regions of the disk atmosphere between the midplane and the upper layer, in accordance with predictions from models of the chemistry in disks. The sizes of the disks were estimated from model fits to the 12 CO 3-2 line profiles. The abu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
271
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(296 citation statements)
references
References 78 publications
19
271
6
Order By: Relevance
“…In the cold mid-plane (< 20 K), most molecules are frozen out onto the grains. This layered chemical structure is consistent with observations of ions and radicals with abundance ratios that are similar or higher than those found in PDRs (e.g., [14,70]). If the UV radiation is energetic enough to dissociate CO, isotope selective processes may occur leading to fractionation of CO isotopes which can eventually be incorporated into meteorites [46].…”
Section: Introductionsupporting
confidence: 89%
“…In the cold mid-plane (< 20 K), most molecules are frozen out onto the grains. This layered chemical structure is consistent with observations of ions and radicals with abundance ratios that are similar or higher than those found in PDRs (e.g., [14,70]). If the UV radiation is energetic enough to dissociate CO, isotope selective processes may occur leading to fractionation of CO isotopes which can eventually be incorporated into meteorites [46].…”
Section: Introductionsupporting
confidence: 89%
“…To correct the observed emission line brightness temperatures for beam dilution, we assume that (Thi et al 2004)…”
Section: Appendix A: Individual Galaxies Appendix B: Beam/source Coupmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition, both ethanol and OH have been detected in interstellar molecular clouds and star forming regions (hot and cold cores) such as W3(OH) and Sgr B2, where temperatures can reach as low as 40 K. [7][8][9][10][11][12][13] Millar et al 12 suggested that ethanol could potentially be used as a chemical clock for hot cores if the kinetics of its reactions with species including the hydroxyl radical were better understood at temperatures pertinent to such environments. Conducting kinetic studies with species known to be present in these cold environments is important for the advancement of chemical models of these regions.…”
Section: Introductionmentioning
confidence: 99%